IMPACT OF TRADE WARS ON GLOBAL ECONOMIC GROWTH: THE CASE OF UZBEKISTAN - Kosimov Shokhrukhbek Ilxomjon ugli; Dr. H. Amir Machmud (Innovation Science and Technology, 2025)
This essay examines the inﬂuence of international trade conﬂicts on the economic development of Uzbekistan a Central Asian developing country undergoing major economic reforms and international integration. The analysis focuses on trade volumes, foreign direct investment (FDI) inﬂows, and price stability. In recent years, trade wars characterized by increased tariﬀs, punitive measures, and disrupted global supply chains have become more prevalent, particularly between major powers such as the United States and China. Using a mixed-methods approach, the study combines quantitative data analysis with qualitative insights from interviews with economists and policy experts. Time-series economic data from 2010 to 2024 were used to correlate key national indicators with global trade tensions. Concurrently, expert interviews contextualized the statistical fndings and deepened understanding of how trade policies and economic responses evolve during periods of global instability.